2014
DOI: 10.1088/0004-637x/788/2/137
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Magnetic Elements in a Supergranular Cell

Abstract: Small scale magnetic fields (magnetic elements) are ubiquitous in the solar photosphere. Their interaction can provide energy to the upper atmospheric layers, and contribute to heat the solar corona. In this work, the dynamic properties of magnetic elements in the quiet Sun are investigated. The high number of magnetic elements detected in a supegranular cell allowed us to compute their displacement spectrum (∆r) 2 ∝ τ γ (being γ > 0, and τ the time since the first detection), separating the contribution of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(71 citation statements)
references
References 36 publications
6
63
0
2
Order By: Relevance
“…From these two plots we can deduce that 1) the smaller the r 0 , the smaller the effective eddy diffusivity Δr 2 /τ for any τ; and 2) the smaller the r 0 , the smaller the value of the effective slope γ; in addition, there is a clear change in the trend for initial separation crossing the value r 0 ∼ 10 Mm, which roughly corresponds to the radius of the ROI. From an observational point of view, 1) and 2) could be interpreted by taking into account the recent results in Orozco Suárez et al (2012) and Giannattasio et al (2014). In those works, the authors showed that the horizontal velocity field within a supergranule is mostly radial and directed from the center to the boundaries.…”
Section: Resultsmentioning
confidence: 86%
“…From these two plots we can deduce that 1) the smaller the r 0 , the smaller the effective eddy diffusivity Δr 2 /τ for any τ; and 2) the smaller the r 0 , the smaller the value of the effective slope γ; in addition, there is a clear change in the trend for initial separation crossing the value r 0 ∼ 10 Mm, which roughly corresponds to the radius of the ROI. From an observational point of view, 1) and 2) could be interpreted by taking into account the recent results in Orozco Suárez et al (2012) and Giannattasio et al (2014). In those works, the authors showed that the horizontal velocity field within a supergranule is mostly radial and directed from the center to the boundaries.…”
Section: Resultsmentioning
confidence: 86%
“…Our internetwork γ value is larger than those reported in the literature. In addition to those mentioned above, examples of diffusion indices of internetwork magnetic features are γ=1 (Utz et al 2010), γ=0.96 (Manso Sainz et al 2011), γ=1.59 (Chitta et al 2012, γ=1.20-1.34 (for different length scales; Giannattasio et al 2013), γ=1.69 (PaperI), and γ=1.44 (Giannattasio et al 2014). We note that the γ value in PaperI was determined from migration of magnetic bright points in both internetwork and vicinity of network areas.…”
Section: Discussionmentioning
confidence: 98%
“…2 was realized by computing the displacement of magnetic elements from the long-duration (∼25 h) data set acquired by Hinode-NFI (Kosugi et al 2007;Tsuneta et al 2008) and used in the analysis by Giannattasio et al (2013Giannattasio et al ( , 2014a. The spatial resolution of this data set is 0.…”
Section: Real Datamentioning
confidence: 99%
“…The tracking algorithm used for the two data sets is the same used in Giannattasio et al (2013Giannattasio et al ( , 2014a and presented in Del Moro (2004) and Berrilli et al (2005). These two data sets combined allow us to explore more consistently the time range from 5 s to 10 000 s. They consistently identify a superdiffusive behaviour (γ 1.4) in the overlapping time range 90 s ≤ t < 500 s. We stress that, to our knowledge, this is the first time that two data sets acquired with rather different instruments and at different sites agree on retrieving γ values consistent within the errors.…”
Section: Real Datamentioning
confidence: 99%
See 1 more Smart Citation